Digital curation: Learning and legacy in later life. (March 2015) - Manchester, Helen; Facer, Keri
The world population is ageing. In the UK alone, it is projected that by 2035 those aged 65 and over will account for 23 per cent of the total population whilst the number of people aged 85 and over will account for 5 per cent of the total population. At the same time, the digital transformations of the last few decades are leaving behind many older adults who, for reasons ranging from accessibility issues to work biographies to personal preference, are less likely to engage with digital technologies. Research undertaken in this area to date has largely been policy led and concerned with providing hardware access and basic skills (e.g. Race Online in the UK). In this article we are concerned with the powerful capacities of digital technologies for communication, archiving, and self-representation, which are under-used by this group, meaning that their cultural histories and experiences are often less visible in the digital world (Loe, 2013 ;Potter, 2013 ). While large digital companies such as Google are beginning to consider and provide resources to help people to plan for their 'digital afterlife' (Graham et al., 2013) – mainly restricted to issues of specifying what happens to social media presence and email accounts after death – there is little work that examines older people's experiences of attempting to use the digital to tell stories that will leave a personal and public legacy towards the end of life. This article begins to examine the challenges and the opportunities that might characterise this area. In doing so, it explores two research studies with 'third' and 'fourth' agers that have examined, in very different settings, the diverse challenges of knitting together the fragmented and scattered 'data' of life experience into private and public narratives. The first study is a case study of three community filmmakers working with an artist to create a film based on their peers' experiences as first generation Caribbean immigrants to the UK; the second is a study comprising three workshops and five detailed case studies examining how older adults use existing 'data' to recollect, to curate and to reflect on their lives and learning for personal purposes.